Educational Research Orientations in the field of Curricula and Teaching Methods of English Language in Arab World during the Period 2020-2022 - Al-Khathami, Fawzeyah Khafeer; Al-Saeedi, Hanan Ahmad (Journal of Curriculum and Teaching Methodology, 2023)
The current research aimed to investigate thematic and methodological orientations of educational researches in the field of English curricula and teaching methods in Arab World from 2020 to 2022 in Almandumah database. To achieve this objective, the researcher used the bibliometric method to analyze (214) researches, (60) master theses, and (21) doctorate theses. As for the thematic orientations, the results showed that the most targeted school stage by the researchers is the secondary stage. In the field of teaching strategies, methods and models, the research targeted the teaching strategies based on the effort of the teacher and the learner. In the field of the teacher, the researches aimed at evaluating the performance of the English language teacher, and in the field of the learner, the research focused on studying the difficulties facing the learner of the English language. As for the field of the course, the analysis of the content of the English language course in the light came in the first rank, while the research, in the field of activities, focused on evaluating the activities of the English language curriculum. The most targeted language content was reading skills. As for the methodological orientations, the results showed that researches targeted individual and applied research. Also, most of the researches followed the quantitative method. As for the research designs, the experimental research obtained the highest frequency among the other designs. With regard to data collection tools, the test was the most used tool by researchers, while the school students category got the highest frequency in relation to other groups in the research population. In light of the results of the research, the researcher presented a research map that identifies research priorities in the field of curricula and methods of teaching English language, and she also presented a number of recommendations and proposals.